Antithrombotic agents for primary and secondary prevention of cardiovascular events in patients with end-stage renal disease on chronic hemodialysis. (April 2020) - Königsbrügge, Oliver; Schmaldienst, Sabine; Auinger, Martin; Klauser-Braun, Renate; Lorenz, Matthias; Tabernig, Susanne; Kletzmayr, Josef; Enzenberger, Brigitte; Eigner, Manfred; Hecking, Manfred; Siller-Matula, Jolanta M.; Pabinger, Ingrid; et al.
Abstract: Background and aims: Cardiovascular disease (CVD) is common in patients with end-stage renal disease (ESRD) on hemodialysis (HD). However, antithrombotic therapy to prevent CVD increases the risk of bleeding. We aimed to investigate the prevalence of CVD and the practice patterns of antithrombotic agents in patients with ESRD on HD. Methods: In a cross-sectional population based cohort of chronic HD patients (n = 626) from Vienna, Austria, the medical histories of patients and use of antithrombotic treatment were recorded, and the distribution of antithrombotic therapies for primary (n = 260, 41.5%) or secondary (n = 366, 58.5%) prevention of CVD was analyzed. Results: Single antiplatelet therapy (SAPT) was used in 234 patients (37.4%), dual antiplatelet (DAPT) in 50 (8.0%), combination of anticoagulation and antiplatelet in 59 (9.4%), anticoagulation monotherapy in 78 (12.5%), and no antithrombotics in 205 patients (32.7%). The prevalence of CVD was 58.5%. In primary CVD prevention, 23.5% (n = 61) of patients were treated with SAPT. For secondary prevention, SAPT was used in 173 (47.3%), DAPT in 49 (13.4%), and dual antithrombotic therapies in 50 patients (13.7%), while 55 (15.0%) patients received no antithrombotics. Age (odds ratio [OR] per 1 year increase 0.96, 95%CI 0.94–0.99, p = 0.004) and hereditary nephropathy (OR 4.13, 95%CI 1.08–15.78, p = 0.038) were independently associated with the absence of antithrombotic therapy in secondary CVD prevention. Conclusion: The majority of patients did not receive antithrombotic therapy for primary prevention. Only 15% did not receive antithrombotic agents in the secondary prevention setting. The net-clinical benefit of antithrombotic therapy in ESRD needs to be determined. Graphical abstract: Image 1 Highlights: Patients on hemodialysis are a neglected population regarding cardiovascular disease (CVD) prevention. In this cross-sectional population-based cohort, 23.5% of patients received antiplatelet agents in primary CVD prevention. In secondary CVD prevention, 15.0% of patients received no antithrombotics. Patients receiving no antithrombotics were more likely to be younger and to have hereditary nephropathy.